ANALISIS BERAKHIRNYA KERJA SAMA ANTARA INDONESIA-NORWEGIA DALAM PROGRAM REDUCING EMISSION FROM DEFORESTATION AND FOREST DEGRADATION (REDD+) - Joel Fariz Nair (2023)
Environmental problems began to become serious problems since their impacts were felt by humans. These environmental problems are causing climate change to happen faster than it should. Because the environment, especially forests, has an important role in the mitigation of climate change. However, forests in the world from year to year are declining due to deforestation, forest degradation, and other problems. Therefore, countries around the world are creating REDD+ programs in an effort to save the world's forests. As the country with the third largest tropical forest in the world, Indonesia has potential in REDD+. In 2010 Indonesia and Norway signed a Letter of Intent (LOI) cooperation in the REDD+ program. However, the cooperation had to stop because in September 2010 Indonesia terminated the cooperation. This study aims to determine the causes of the end of REDD+ cooperation between Indonesia and Norway. Data are collected through the study of literature. This research uses the concept of national interest and green political theory. The results of this study seek to explain the reasons that led to the end of REDD+ cooperation between Indonesia and Norway.